Strengthening the Legal Awareness of the Nambo Village Community in Supporting Social Reintegration for Former Correctional Inmates - Dwi Afrimetty Timoera; Annisa Rahmi Faisal; Sanusi Sanusi; Aditya Affandi; Fikri Luhur Dwi Putro; Peni Pinandhita; Rafa' Rafa'; Sekar Sakinatus Saadah; Widya Tjandra (Universitas Negeri Malang, 2026)
The purpose of this study is to analyze the social reintegration of former inmates from a legal perspective, as well as the strategies and challenges faced in the process of social reintegration for former inmates. This study employs a qualitative approach using phenomenological methods. The results of the study indicate that social reintegration already has a legal basis as stipulated in Law Number 22 of 2022 on Correctional Institutions, which emphasizes rehabilitation, the protection of human rights, and the restoration of the social functions of former inmates. Strategies to strengthen social reintegration are implemented through legal education, participatory dialogue, legal awareness campaigns, and the involvement of village governments and communities in building an inclusive social environment. Challenges in the reintegration process include social stigma, negative stereotypes, low community legal literacy, limited economic access, and a lack of space for social dialogue between the community and former inmates.